2020
DOI: 10.1177/0972063420938471
|View full text |Cite
|
Sign up to set email alerts
|

Participants’ Perspectives on Healthcare Service Quality in Multispecialty Hospitals: A Qualitative Approach

Abstract: Professional services like healthcare operate with high degree of information asymmetry, where usually the seeker of service lacks knowledge and skills, and as a result, they cannot evaluate the benefits. Alternative indicators in the service delivery are sought by the seekers to bring evenness in their evaluation, which might not be reflective of providers’ perspectives of care. This study attempts to explore perspectives of both the participants in healthcare service delivery in multispecialty hospital setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Service delivery refers to the social aspects of the physical environment (Jessup et al, 2020) including service mannerisms such as empathy, friendliness, and kindness toward the patients (Upadhyai et al, 2020). It is evaluated differently compared to other service environments like restaurants, banks, or airlines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Service delivery refers to the social aspects of the physical environment (Jessup et al, 2020) including service mannerisms such as empathy, friendliness, and kindness toward the patients (Upadhyai et al, 2020). It is evaluated differently compared to other service environments like restaurants, banks, or airlines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is a particularly salient finding as healthcare operates with a high degree of information asymmetry, where patients often lack knowledge to evaluate the benefits and side effects of treatment. 37 Research has found that shared decision making (SDM), a model of interaction between providers and patients in which both participants contribute to the medical decision-making process, and the provider explains the benefits and risks of each treatment option, improves medication adherence. 38 Further, qualitative research has found that patient education efforts, physician training in interpersonal skills, and efforts to engage patients in SDM may positively impact mistrust of physicians in racial/ethnic minority populations and help improve medication adherence and diabetes outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…HSQ is usually evaluated as the gap between health care seekers' expectations and their perception of performance. The dimensions on which HSQ is measured vary from being unidimensional to as large as having ten dimensions [2]. SERVQUAL is a widely used instrument to measure the service quality gap between customer expectations and perceptions on five dimensions [3].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, patients/attendants are left with no option but to believe in what they have been informed of or delivered. The patient/attendant is considered as a layman in evaluating the fundamental medical/clinical care [2]. HSQ evaluations, therefore, tend to be biased toward a process of delivery and physical settings of hospitals that a patient/attendant can easily evaluate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation